(untitled) (Bangladesh Heart Journal, 2022)
Congenitally Corrected Transposition of Great Arteries (c-TGA) is an anomaly with atrioventricular and ventriculoarterial discordance where left atrium connects to right ventricle and right atrium to left ventricle. However in this case of double inversion, aorta carries saturated blood and pulmonary artery carries venous blood. So, normal physiological circulation is maintained. Our patient, a 38-years-old Bangladeshi male presented with palpitation, dizziness and effort intolerance (NYHAII) during exertion since childhood, which has recently become much worse. However, he had no history of central cyanosis, chest pain or syncope. We diagnosed him as a case of Corrected TGA and second-degree AV block with intermittent complete heart block. A Dual chamber permanent Pacemaker was inserted without any complications. No invasive treatment including corrective surgery was performed because patient’s cardiac function was almost normal. Patient became totally asymptomatic after pacemaker implantation Bangladesh Heart Journal 2022; 37(1): 77-80